The Phospho-Code Determining Circadian Feedback Loop Closure and Output in Neurospora - Wang, Bin (Mol Cell, 2019)
In the negative feedback loop driving fungal and animal circadian oscillators, negative elements (FRQ, PERs, CRYs) are understood to inhibit their own expression in part by promoting the phosphorylation of their heterodimeric transcriptional activators (e.g. WC-1/WC-2 (WCC), BMAL1/CLOCK). However, correlations between heterodimer activity and phosphorylation are weak, contradictions exist, and mechanistic details are almost wholly lacking. We report mapping of 80 phosphosites on WC-1 and 15 on WC-2, and elucidation of the time-of-day-specific code, requiring both a group of phosphoevents on WC-1 and two distinct clusters on WC-2, that governs circadian repression, leading to feedback loop closure. Combinatorial control via phosphorylation also governs rhythmic WCC binding to the promoters of clock-controlled genes mediating the essential first step in circadian output, a group encoding both transcription factors and signaling proteins. These data provide a basic mechanistic understanding for fundamental events underlying circadian negative feedback and output, key aspects of circadian biology.